Selenicereus undatus (Dragon Fruit) Phytochemicals for Managing Three Human Pathogenic Bacteria: An In Vitro and In Silico Approach - Zhuan-Ying Yang; Xue-Wen Zheng; Wen-Hao Jiang; Gui-Zhi Chen; Qing-Zhi Liang; Guang-Zhao Xu; Run-Hua Yi (Metabolites)
Objectives: Antibiotic-resistant bacterial infections are a growing global concern. A natural remedy for bacterial infections could be available in the Selenicereus undatus fruit, but its antibacterial and biochemical properties are not fully known. Methods: In this study, the biochemical composition and antibacterial, antioxidant, and cytotoxic activities of the Jindu No. 1 (JD) and Bird’s Nest (YW) dragon fruit varieties and their potential effects against E. coli, Pseudomonas sp., and Staphylococcus sp. were scrutinized. Results: The JD fruit extract showed higher antibacterial activity than the YW variety against E. coli, Pseudomonas sp., and Staphylococcus sp. in vitro. Additionally, the JD variety demonstrated more significant antioxidant activity than the YW variety and showed less cytotoxic activity. The JD variety had a higher glucose content, while the YW variety had a higher fructose content, and the phytoconstituents analysis confirmed 659 metabolites in total from the two varieties. Through in silico analyses, phytoconstituents were evaluated to identify potential drug molecules against the selected bacterial strain. Moreover, the molecular docking study revealed that riboprobe and Z-Gly-Pro might be effective against E. coli, 4-hydroxy retinoic acid, and that succinyl adenosine may target Pseudomonas sp., and xanthosine and 2′-deoxyinosine-5′-monophosphate may be effective against Staphylococcus sp. These results were further validated by 100 ns Molecular Dynamics (MD) simulation, and all of the selected compounds exhibited acceptable ADMET features. Conclusions: Therefore, phytoconstituents from S. undatus fruit varieties could be employed to fight human bacterial diseases, and future studies will support the continuation of other biological activities in medical research.